2020
DOI: 10.1051/epjap/2020200193
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically driven liquid wicking: numerical study and experimental validation

Abstract: Liquid film or drop wicking on solid surface without any external energy input is highly desirable in specific industrial processes. This paper proposes a numerical study of the dynamics of liquid wicking on geometrically structured flat surface. We consider structures deduced from flat surface by super-imposing a series of identical parallel channels, the ensemble being made of the same material. Channels exhibit arrow-shaped patterns. We analyse drop wicking on such a structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…However, at the mesoscopic scale, it is still relevant to consider the contact angle θ [45]. Therefore, following [42] we assume that the contact angle during the front dynamics is equal to the static contact angle θ. Equations of the VOF method are detailed in the present framework in [37].…”
Section: Physical Model and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the mesoscopic scale, it is still relevant to consider the contact angle θ [45]. Therefore, following [42] we assume that the contact angle during the front dynamics is equal to the static contact angle θ. Equations of the VOF method are detailed in the present framework in [37].…”
Section: Physical Model and Numerical Methodsmentioning
confidence: 99%
“…However, none of these references have attempted to simulate the time evolution of liquid drops far from quasi-static regime in complex geometries such as the fin-shaped structures considered by [16] nor a periodic distribution of tilted pillars [18]. A presentation of the experiment and a first numerical analysis reported in [37] suggested that the fluid inertia cannot be neglected during the wicking. Simulating a free flow surface wetting dynamics with the complete Navier-Sotkes in a complex geometry is a challenging task.…”
Section: Introductionmentioning
confidence: 99%